2011
DOI: 10.1007/s12630-011-9505-7
|View full text |Cite
|
Sign up to set email alerts
|

Cauda equina syndrome following combined spinal and epidural anesthesia: a case report

Abstract: This case suggests that spinal anesthesia, even with an ordinary dose of hyperbaric 0.5% bupivacaine, might induce cauda equina syndrome in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…One multicenter study found that the incidence of TNS was approximately 8.1%, which resulted in pain or sensory abnormalities in the lower back, buttocks, or lower extremities, with symptoms beginning after spinal anesthesia and lasting for hours to 4 days [5]. Although there is low incidence of anesthetic-induced cauda equina syndrome, it results in severe damage to neurons [6]–[8].…”
Section: Introductionmentioning
confidence: 99%
“…One multicenter study found that the incidence of TNS was approximately 8.1%, which resulted in pain or sensory abnormalities in the lower back, buttocks, or lower extremities, with symptoms beginning after spinal anesthesia and lasting for hours to 4 days [5]. Although there is low incidence of anesthetic-induced cauda equina syndrome, it results in severe damage to neurons [6]–[8].…”
Section: Introductionmentioning
confidence: 99%
“…such as cauda equina syndrome [1,21], which raises concerns for its use. Although the pathogenesis for bupivacaine-induced neurotoxicity is unclear, several studies have shown that bupivacaine-induced neuronal damages may be attributed to neuron apoptosis.…”
Section: Groupmentioning
confidence: 99%
“…However, many neurological spine disorders post spinal anesthesia have been caused by such local anesthetics, even at normal clinic dose, leading to neurological complications such as permanent nerve damage and cauda equina syndrome (CES) [1][2][3]. Although the incidence of local anesthetics-induced neurotoxicity is less than 0.04% [4,5], the resultant neural dysfunctions incur a low-quality life and an economic burden to the affected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition to urinary retention, the neurological symptoms can include fecal incontinence, perianal hypoesthesia, and possibly a negative MRI, as reported by Kato et al 8 As for MRI findings, however, in one case report of a patient with transient neurologic symptoms, enhancement of the mildly thickened cauda equina and lumbosacral nerve roots on a post contrast study was described as being attributed to lidocaine neurotoxicity. 10 MRI in viral myeloradiculitis may also show varying degrees of root or lower spinal cord edema with enlargement and hypersensitivity on T2-weight images in some patients, 4 though this was normal in our patient.…”
Section: Discussionmentioning
confidence: 97%